Health Implications of Anabolic-Androgenic Steroids: Usage, Risks, and Treatment Approaches - The Literature Review - Krzysztof Jodłowski; Ewa Dubniewicz; Paula Majewska; Alicja Staszek; Wiktoria Łoskot; Jan Szwech; Mateusz Matczak; Karol Jasiński; Aleksandra Broda; Kacper Hoksa (Quality in Sport)
Anabolic-androgenic steroids (AAS) are commonly used to enhance athletic performance and physical appearance, but their abuse is linked to a range of serious health consequences, including cardiovascular, liver, and psychological disorders, as well as infertility. Despite the growing concern over AAS misuse, current research is limited by methodological constraints, including a lack of randomized controlled trials and long-term studies. The review explores the health implications of AAS use, highlighting the importance of an interdisciplinary approach to managing AAS-related health issues, emphasizing harm reduction, pharmacological interventions, and fertility preservation techniques. It also underscores the need for improved healthcare support, education, and trust-building to address the challenges associated with AAS abuse effectively.